DYNAMICS OF PROCALCITONIN AT THE PATIENT AFTER COMBINED ORGAN TRANSPLANTATION - M. Sh. Khubutia; V. P. Nikulina; A. V. Pinchuk; M. A. Godkov (Вестник трансплантологии и искусственных органов)
Case report represents two episodes of procalcitonin elevation in dynamics, connected with different induction mechanisms of this sepsis marker at the patient after combined pancreas and kidney transplantation.